2018
DOI: 10.52358/mm.v1i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Promoting pre- and in-service teachers’ co-construction of knowledge through an intercultural telecollaboration project

Abstract: This paper reports an intercultural telecollaboration project between four pre- and in-service second/foreign language teachers that sought to analyze how knowledge was co-constructed among team members through online social negotiation. Data consisting of transcripts of two conversations using the conferencing platform Skype were analyzed using a taxonomy adapted from Gunawardena, Lowe and Anderson’s (1997) model.  It was found that the highest amount of utterances (62%) fell into Phase I (Sharing/comparing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These participants started from basic levels of knowledge construction (e.g., describing or exploring teaching event) and progressed to more advanced levels (e.g., interpreting or critiquing teaching events). In a recent telecollaborative project, Ciampi et al [15] documented how several PTs or ITs co-constructed knowledge during online synchronous discussions. Data analysis showed these teachers' Skype utterances primarily focused on lower levels of the creation of meaning, yet comparatively, these teachers produced more statements about the negotiation of meaning than what had been found in previous research.…”
Section: Cross-tier Teacher Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These participants started from basic levels of knowledge construction (e.g., describing or exploring teaching event) and progressed to more advanced levels (e.g., interpreting or critiquing teaching events). In a recent telecollaborative project, Ciampi et al [15] documented how several PTs or ITs co-constructed knowledge during online synchronous discussions. Data analysis showed these teachers' Skype utterances primarily focused on lower levels of the creation of meaning, yet comparatively, these teachers produced more statements about the negotiation of meaning than what had been found in previous research.…”
Section: Cross-tier Teacher Professional Developmentmentioning
confidence: 99%
“…It is because PTs usually lack sufficient pedagogical skills and ITs often receive less training on the uses of technology application. Comparatively, less research has recruited both preservice and inservice language teachers to join the same learning community (e.g., [13,15,40]). Relying solely on web-based interaction and discussion, language teachers in these extant studies strengthened one another's instructional knowledge, skills, or activities, while Chen [13] further reported that PTs shared with ITs how to effectively utilize technology tools.…”
Section: Introductionmentioning
confidence: 99%